Can Transparency In Shareholders' Right Allocation Minimize Creative Accounting and Agency Conflict? - Kusumaningarti, Miladiah; Kusuma, Marhaendra; Ahmad, Abdul Hadi Bin; Santos, Alfredo Dos (Program Studi Akuntansi FPEB UPI, 2025)
This study examines the agent-principal and majority-minority principal interest relationships in creative accounting and examines the moderating role of transparency in allocation of rights in these relationships. A sample of 540 companies listed on the Indonesian Stock Exchange (IDX) from 2020 to 2024 with observational data of 2,641 firm-years. Result show that transparency in profit allocation rights can weaken the emergence of agency problems and creative accounting in the form of earnings management. Robustness test results show consistent results when creative accounting is measured by income smoothing. Additional test results indicate that transparency in equity allocation rights also contributes to weakening agency conflicts and creative accounting. This study is original, examining whether type 1 and type 2 agency problems can spur the emergence of creative accounting, and whether transparency in the allocation of rights to net income and assets can weaken the emergence of creative accounting.